Comparison among the efficacy of interventions for the return rate to receive the pap test report: randomized controlled clinical trial - Camila Teixeira Moreira Vasconcelos; Ana Karina Bezerra Pinheiro; Ana Izabel Oliveira Nicolau; Thaís Marques Lima; Denise de Fátima Fernandes Barbosa
ABSTRACT Objective: to test the effects of a behavioral, an educative and a comparative intervention on women's adherence to the return appointment to receive the pap test report. Methods: randomized controlled clinical trial at a Primary Health Care Service, involving three groups: EG (educative session and test demonstration), BG (recall ribbon) and standard intervention (card containing the return appointment - graphical reminder), called comparative group here (CG). To select the sample, the following was established: having started sexual activity and undergoing the pap smear during the study, resulting in 775 women. Results: among the 775 women, 585 (75.5%) returned to receive the test result within 65 days. The educative group presented the highest return rate (EG=82%/CG=77%/BG=66%), statistically significant only when compared to the behavioral group (p=0.000). The educative group obtained the smallest interval (p<0.05) concerning the mean number of days of return to receive the test result (EG:M=43days/BG:M=47.5days/CG:M=44.8 days). Conclusion: the educative group reached higher return rates and the women returned earlier, but the behavioral intervention showed to be the least effective. Brazilian Clinical Trial Register: RBR-93ykhs.